Perancangan Aplikasi Tour Travel Nusa Tenggara Timur Berbasis Web - Kewa Nilan, Yasinta Anita; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023, 2023)
East Nusa Tenggara (NTT) is a province in Indonesia which is rich in natural beauty, culture, and history. Even though NTT has tremendous tourism potential, challenges in the promotion and accessibility of tourist destinations are still a major concern. In today's digital era, web-based applications are tools that effectively facilitate the tourism industry by providing complete information, facilitating travel planning, and expanding the reach of promotions. Therefore, this web-based NTT travel tour application makes it easy for tourists to access information, compare options, and plan trips efficiently.